Photothermal interface evaporation-photocatalytic hydrogen production composite material and its preparation method and application

By loading ink and hydrophobic agent on the water-absorbing sponge, combined with Al-doped SrTiO3 nanoparticles with Rh/Cr2O3 cocatalyst, the problems of high band gap and seawater corrosion in full water-removing hydrogen production were solved, and the solar spectrum was realized The frequency-dividing utilization and fresh water resources have improved the efficiency of hydrogen production.

CN118874462BActive Publication Date: 2025-01-03CHANGAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411338004.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-03
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing SrTiO3-based photocatalysts are limited by high band gap and seawater corrosion problems during the full water-removal hydrogen production process, resulting in low energy utilization efficiency and shortage of freshwater resources, making it difficult to apply on a large scale.

Method used

Using a water-absorbing sponge as the substrate, loading ink and hydrophobic agent to form a sponge-ink self-floating evaporator, and Al-doped SrTiO3 nanoparticles loaded with Rh/Cr2O3 cocatalyst, realize efficient frequency division of the solar spectrum and drive seawater Interfacial evaporation and photocatalytic total water dissolution.

Benefits of technology

It realizes efficient utilization of the full spectrum of solar light, obtains fresh water and hydrogen, and avoids seawater corrosion of SrTiO3-based photocatalysts, overcomes freshwater dependence, and improves the efficiency of hydrogen production in full water removal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118874462B_ABST
    Figure CN118874462B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of new energy materials and devices, specifically to a photothermal interface evaporation-photocatalytic hydrogen production composite material and a preparation method and application thereof. The present invention uses a water-absorbing sponge as a substrate and ink as a photothermal material. After the ink is adsorbed on the water-absorbing sponge, a hydrophobic agent and a photocatalyst are sequentially loaded on the ink to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material, wherein the photocatalyst is Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalysts. The photothermal interface evaporation-photocatalytic hydrogen production composite material uses low-energy photons in the solar spectrum to drive seawater interface evaporation to obtain fresh water resources, and uses high-energy photons in the solar spectrum to drive photocatalytic full water decomposition to produce hydrogen, thereby realizing efficient frequency division utilization of the full spectrum of sunlight, and simultaneously obtaining fresh water and producing hydrogen in the process of solar energy conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new energy materials and devices, in particular to a photothermal interface evaporation-photocatalytic hydrogen production composite material and a preparation method and application thereof. Background Art

[0002] The development and utilization of clean renewable energy is an important issue in solving future energy needs. Solar energy is abundant and widely distributed, and is the most promising renewable energy source. However, due to its low energy density, discontinuity in time and space, and difficulty in direct storage, it has greatly limited the large-scale utilization of solar energy. Hydrogen energy has the advantages of high energy density and cleanness and is considered to be a future energy carrier that complements electric energy. It will play a key role in the future clean energy system. Solar-driven photocatalytic water splitting technology is a conversion and storage technology that uses photocatalysts to convert solar energy into hydrogen energy.

[0003] The principle of semiconductor photocatalytic water splitting to produce hydrogen is: semiconductor photocatalysts absorb photons with energy greater than their band gaps, are excited to produce photogenerated electron-hole pairs, and then separate and migrate to the surface of the catalyst. Finally, the photogenerated electrons and holes that migrate to the active sites on the surface of the photocatalyst undergo reduction and oxidation reactions with water to produce hydrogen and oxygen, respectively. Among the photocatalyst materials reported so far, Al-doped strontium titanate has suitable valence band and conduction band positions, has the ability to produce hydrogen and oxygen simultaneously, and has a wide range of raw material sources and a stable structure. It has attracted much attention in the field of photocatalytic water splitting in recent years.

[0004] However, its large-scale application is still subject to many restrictions at this stage. From an energy perspective, it is limited by its wide band gap of 3.2eV. The photon energy required for the complete water splitting of SrTiO3-based photocatalysts is relatively high. It can only utilize ultraviolet light, which accounts for 4% of the total energy in the solar spectrum, while the energy in the visible and infrared bands of the solar spectrum has not been fully utilized and converted.

[0005] From a material perspective, when the existing technology uses SrTiO3-based photocatalysts to completely split seawater into hydrogen, the SrTiO3-based photocatalyst needs to be immersed in seawater, which is limited by the fact that seawater decomposition produces Cl2 and ClO. - , which leads to the problem of oxidative corrosion of SrTiO3-based photocatalysts. Therefore, the main source of material for SrTiO3-based photocatalysts to produce hydrogen through complete water splitting is still fresh water. However, fresh water resources are in short supply, so it is necessary to develop a method that can achieve complete water splitting to produce hydrogen without using fresh water. Summary of the invention

[0006] In view of the deficiencies of the above-mentioned prior art, the present invention provides a photothermal interface evaporation-photocatalytic hydrogen production composite material and its preparation method and application. The present invention uses a water-absorbing sponge as a substrate and ink as a photothermal material. After the ink is adsorbed on the water-absorbing sponge, a hydrophobic agent is loaded on the ink to obtain a sponge-ink self-floating evaporator, and a photocatalyst is loaded on the sponge-ink self-floating evaporator to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material. The photocatalyst is Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalysts. The photothermal interface evaporation-photocatalytic hydrogen production composite material uses low-energy photons in the solar spectrum to drive seawater interface evaporation to obtain fresh water resources, and uses high-energy photons in the solar spectrum to drive photocatalytic full water decomposition to produce hydrogen, thereby realizing efficient frequency division of the full spectrum of sunlight, and obtaining fresh water while producing hydrogen by electrolysis of seawater; in addition, the sponge-ink self-floating evaporator avoids the immersion of the SrTiO3-based photocatalyst in fresh water, overcoming the technical defects existing when the SrTiO3-based photocatalyst is used to produce hydrogen by full water decomposition of seawater.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] The preparation method of the photothermal interface evaporation-photocatalytic hydrogen production composite material comprises the following steps:

[0009] The absorbent sponge is used as a base, and is immersed in ink so that the bottom of the absorbent sponge absorbs the ink, and then dried to obtain a treated absorbent sponge.

[0010] After the hydrophobic agent polydimethylsiloxane is dispersed, a hydrophobic agent solution is obtained.

[0011] The hydrophobic agent solution is attached to the ink treated with the water-absorbing sponge, and then dried to obtain a sponge-ink self-floating evaporator.

[0012] After the photocatalyst is dispersed, it is attached to the hydrophobic agent of the sponge-ink self-floating evaporator to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material.

[0013] The photocatalyst is Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalyst.

[0014] Preferably, the mass ratio of the volume of the sponge-ink self-floating evaporator to the photocatalyst is (3.5cm×3.5cm×1cm): 20mg~150mg. The loading amount of the photocatalyst on the sponge-ink self-floating evaporator is obtained through experimental research. The results show that too little loading amount of the photocatalyst is not conducive to the electrolysis of water to produce hydrogen, and too much loading amount of the photocatalyst is not conducive to the evaporation of water.

[0015] Preferably, a curing agent is also added during the preparation of the hydrophobic agent solution. The curing agent is polydimethylsiloxane with hydroxyl groups. The curing agent enables the hydrophobic agent to be stably attached to the ink. The mass ratio of the curing agent to the hydrophobic agent is 1:10-20.

[0016] Preferably, the photocatalyst is prepared according to the following steps:

[0017] SrTiO3 nanoparticles were prepared by hydrothermal method using aqueous strontium nitrate solution and ethylene glycol solution of tetra-n-butyl titanate as raw materials.

[0018] SrTiO3 nanoparticles and alumina are used as raw materials, and strontium chloride is used as molten salt. After grinding and mixing evenly, the mixture is calcined at high temperature, and the SrTiO3 nanoparticles are grown again in a molten state to grow into Al-doped SrTiO3 nanoparticles with a cubic morphology.

[0019] Al-doped SrTiO3 nanoparticles are ultrasonically dispersed in a solvent to obtain a dispersion, and then a Na3RhCl6 solution is added thereto, and Rh is photodeposited on the Al-doped SrTiO3 nanoparticles after light irradiation. Then a K2CrO4 solution is added to the dispersion, and Cr2O3 is photodeposited on the Al-doped SrTiO3 nanoparticles after light irradiation to obtain a photocatalyst.

[0020] Preferably, the mass percentage of Al-doped SrTiO3 nanoparticles in the dispersion, Rh in the Na3RhCl6 solution, and Cr in the K2CrO4 solution is 100:0.1~0.6:0.05~1. The co-catalyst is the active site for hydrogen production by electrolysis of water. If the amount of the co-catalyst is small, the catalytic activity of the photocatalyst is low. If the amount of the co-catalyst is large, the surface of the Al-doped SrTiO3 nanoparticles is covered, affecting light absorption.

[0021] Preferably, the intensity of light irradiation is 100 mW / cm 2 ~800mW / cm 2 The irradiation time is 10min~60min.

[0022] Preferably, the molar ratio of SrTiO3 nanoparticles, aluminum oxide, and strontium chloride is 1:0.02-1:10-20.

[0023] Preferably, the high temperature calcination condition is: calcination at 1100° C. to 1150° C. for 5 h to 10 h.

[0024] The present invention also protects the use of the photothermal interface evaporation-photocatalytic hydrogen production composite material in the preparation of photocatalytic water splitting to produce hydrogen materials and the preparation of materials for driving seawater interface evaporation.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention constructs a solar-driven photothermal interface evaporation-photocatalytic hydrogen production composite material, which is composed of a sponge-ink self-floating evaporator and a photocatalyst. On the one hand, the sponge-ink self-floating evaporator uses low-energy photons in the solar spectrum, namely, long-wave visible light and infrared light bands, to drive the evaporation of the seawater interface to obtain fresh water resources; the photocatalyst uses high-energy photons in the solar spectrum, namely, short-wave visible light and ultraviolet light bands, to drive photocatalytic water decomposition to produce hydrogen, thereby achieving efficient frequency division of the full spectrum of sunlight, and simultaneously obtaining fresh water and producing hydrogen in the process of solar energy conversion. On the other hand, the photocatalyst is loaded above the hydrophobic agent of the sponge-ink self-floating evaporator and cannot come into contact with seawater. At this time, the fresh water produced by the evaporation of the seawater interface is utilized, thereby overcoming the problem of Cl2 and ClO produced by the decomposition of seawater. - This leads to corrosion problems on SrTiO3-based photocatalysts, but also achieves the purpose of producing hydrogen by fully splitting seawater.

[0027] 2. The present invention provides a photocatalyst, which is Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalysts. The Al-doped SrTiO3 nanoparticles are the main photocatalyst, and the role of the Rh / Cr2O3 co-catalyst is to provide reaction sites to assist the main photocatalyst in decomposing water to produce hydrogen. If the co-catalyst is not loaded, the Al-doped SrTiO3 nanoparticles have basically no photocatalytic hydrogen production activity.

[0028] 3. The present invention uses light irradiation to achieve photodeposition of Rh / Cr2O3 co-catalyst. The principle of photodeposition is to use the semiconductor to absorb photons to generate photogenerated electrons and hole pairs, wherein the photogenerated electrons have reducing properties and can reduce Rh ions in the solution to Rh elemental substances while loading Cr2O3.

[0029] 4. The present invention also provides a sponge-ink self-floating evaporator. The sponge-ink self-floating evaporator uses a water-absorbing sponge as a substrate. The bottom of the water-absorbing sponge is immersed in the ink, and then dried to obtain a treated water-absorbing sponge. The hydrophobic agent solution is attached to the ink of the treated water-absorbing sponge, and then dried to obtain the sponge-ink self-floating evaporator. Therefore, the black part on the surface of the sponge-ink self-floating evaporator is caused by the deposition of carbon nanoparticles in the ink. It is a good light-absorbing material that can fully absorb visible light and infrared light in the solar spectrum and has excellent photothermal properties. It heats the seawater transported to the ink and promotes its rapid evaporation and conversion into water vapor. The present invention also attaches the hydrophobic agent to the carbon nanoparticles to successfully construct a Janus membrane. The Janus membrane is a membrane with two different properties. In the present invention, one side of the Janus membrane is hydrophilic and the other side is hydrophobic. On the one hand, the hydrophobicity of the Janus membrane ensures that it can float on the water surface for a long time and avoid salt accumulation. On the other hand, the hydrophilicity of the Janus membrane can continuously provide seawater to the carbon nanoparticles in the ink, ultimately achieving full water splitting to produce hydrogen and obtain fresh water. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of the principle of using the photothermal interface evaporation-photocatalytic hydrogen production composite material of the present invention to decompose seawater to produce hydrogen and obtain fresh water.

[0031] Figure 2 This is a flow chart for the preparation of Al-doped SrTiO3 nanoparticles in Example 1.

[0032] Figure 3 This is a flow chart for preparing the photothermal interface evaporation-photocatalytic hydrogen production composite material in Example 1.

[0033] Figure 4 In the figure, (a) is the XRD pattern of Al:STO of Example 1, (b) is the XRD pattern of CIMS of Example 1, Al:STO / CIMS-20 of Example 1, Al:STO / CIMS-50 of Example 2, Al:STO / CIMS-100 of Example 3 and Al:STO / CIMS-150 of Example 4; Al:STO is Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalyst, CIMS is a sponge-ink self-floating evaporator, Al:STO / CIMS-20 is Al:STO / sponge-ink self-floating evaporator-20, Al:STO / CIMS-50 is Al:STO / sponge-ink self-floating evaporator-50, Al:STO / CIMS-100 is Al:STO / sponge-ink self-floating evaporator-100, and Al:STO / CIMS-150 is Al:STO / sponge-ink self-floating evaporator-150.

[0034] Figure 5 In the figure, (a) is a SEM image of the Al-doped SrTiO3 nanoparticles of Example 1, and (b) is a TEM image of the Al-doped SrTiO3 nanoparticles of Example 1.

[0035] Figure 6 In the figure, (a) is a top view of Al:STO / CIMS-100 of Example 3, and (b) is a side view of Al:STO / CIMS-100 of Example 3.

[0036] Figure 7 In the figure, (a) is melamine sponge, (b) is CIMS of Example 1, (c) is Al:STO / CIMS-20 of Example 1, (d) is Al:STO / CIMS-50 of Example 2, (e) is Al:STO / CIMS-100 of Example 3, and (f) is the super depth of field image of Al:STO / CIMS-150 of Example 4.

[0037] Figure 8 In the figure, (a) is a contact angle test graph of Al:STO / sponge-ink evaporator-100 without hydrophobic agent in comparative example 1 at 0s, (b) is a contact angle test graph of Al:STO / sponge-ink evaporator-100 without hydrophobic agent in comparative example 1 at 0.4s, (c) is a contact angle test graph of Al:STO / CIMS-100 of embodiment 3 at 0s, and (d) is a contact angle test graph of Al:STO / CIMS-100 of embodiment 3 at 10s.

[0038] Fig. 9 In the figure, (a) is a top view of the Al:STO / sponge-ink evaporator-100 without a hydrophobic agent in comparative example 1, (b) is a side view of the Al:STO / sponge-ink evaporator-100 without a hydrophobic agent in comparative example 1, (c) is a top view of the Al:STO / CIMS-100 of embodiment 3, and (d) is a side view of the Al:STO / CIMS-100 of embodiment 3.

[0039] Fig.10 UV-Vis graphs of Al:STO of Example 3 and Al:STO / CIMS-100 of Example 3.

[0040] Fig.11 In the figure, (a) is the evaporation performance diagram of CIMS of Example 3 and Al:STO / CIMS-100 of Example 3, and (b) is the performance test diagram of full water splitting and hydrogen production of Al:STO / CIMS-100 of Example 3.

[0041] Fig.12It is a bar chart of the hydrogen production rate from the complete water decomposition of CIMS of Example 1, Al:STO / CIMS-20 of Example 1, Al:STO / CIMS-50 of Example 2, Al:STO / CIMS-100 of Example 3 and Al:STO / CIMS-150 of Example 4. DETAILED DESCRIPTION

[0042] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0043] The present invention utilizes solar energy to drive the seawater interface evaporation technology. The solar energy driven seawater interface evaporation technology is to place photothermal materials at the air-seawater interface, utilize the photothermal materials to absorb solar energy and convert it into thermal energy, and heat the water at the gas-liquid interface. It does not need to heat the entire water body to achieve a higher photothermal-steam conversion efficiency. The solar energy driven seawater interface evaporation technology can utilize almost the energy of the entire solar spectrum, which not only improves the conversion efficiency of solar energy, but also solves the problem of freshwater resource shortage. It can also be coupled with photocatalysts to fully decompose water to produce hydrogen, thereby achieving perfect coupling in material and energy conversion.

[0044] The technical solution of the present invention is further explained by using embodiments and comparative examples, as shown below:

[0045] Example 1

[0046] The preparation method of the photothermal interface evaporation-photocatalytic hydrogen production composite material Al: STO / sponge-ink self-floating evaporator-20 comprises the following steps:

[0047] Step 1, preparation of Al:STO:

[0048] SrTiO3 nanoparticles were prepared by a hydrothermal method. The specific process was as follows: Under stirring conditions, 10 mL of a 0.5 mol / L aqueous strontium nitrate solution was added dropwise to a 10 mL of a 0.5 mol / L ethylene glycol solution of tetra-n-butyl titanate, and then 10 mL of a 5 mol / L NaOH solution was added. After stirring for 30 min, a mixed solution was obtained. The mixed solution was transferred to the inner lining of a hydrothermal autoclave with a volume of 100 mL. After sealing, the mixed solution was placed in an oven at 200°C for reaction for 24 h. After the reaction was completed, the mixture was cooled to room temperature. The obtained white precipitate was subjected to multiple centrifugal washing treatments until it was neutral, and finally vacuum dried and collected to obtain SrTiO3 nanoparticles.

[0049] Al:STO was prepared by a molten salt method. The specific process was as follows: SrTiO3 nanoparticles, alumina and strontium chloride were mixed and ground for 30 minutes in a molar ratio of 1:0.02:10 to obtain a mixture. The mixture was then transferred to a corundum crucible and calcined at 1100°C for 5 hours in a muffle furnace at a heating rate of 5°C / min. After the reaction was completed, it was naturally cooled to room temperature and then washed with deionized water to remove the residual strontium chloride. Finally, it was vacuum dried and collected to obtain Al-doped SrTiO3 nanoparticles. The process is as follows Figure 2 shown.

[0050] The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 100 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.3 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 1.0 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.3 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 1.0 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution. 2 After 1 h of xenon lamp irradiation, 0.2 mol / L K2CrO4 solution containing 1 wt% Cr was added and the irradiation was continued at 300 mW / cm 2 The xenon lamp was irradiated for 1 h, and the entire photodeposition process was maintained at 35 o C. After the reaction, the particles were washed with water and vacuum dried to obtain Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalysts, named Al:STO.

[0051] Step 2: Preparation of sponge-ink self-floating evaporator:

[0052] 5 mL of ink was dispersed in a surface dish with a diameter of 5 cm, and a melamine sponge with a size of 3.5 cm × 3.5 cm × 1 cm was immersed in the ink to allow the bottom of the melamine sponge to fully absorb the ink, and then placed in an oven at 80°C for 2 hours to be dried to obtain a treated absorbent sponge. The treated absorbent sponge was a melamine sponge adsorbed with ink.

[0053] 2 mg of polydimethylsiloxane and 0.2 mg of curing agent were ultrasonically dispersed in a mixed solution of 50 mL of ethanol and n-hexane in a volume ratio of 4:1 to obtain a hydrophobic agent solution. The curing agent was polydimethylsiloxane with hydroxyl groups. 3 mL of the hydrophobic agent solution was sprayed on the ink treated sponge by spraying, and then heated in an oven at 120°C for 2 h to obtain a sponge-ink self-floating evaporator, named CIMS.

[0054] Step 3, Preparation of Al:STO / sponge-ink self-floating evaporator-20:

[0055] The coupling system was prepared by a simple spraying method. 20 mg of Al:STO prepared in step 1 was ultrasonically dispersed in 5 mL of ethanol to obtain a dispersion. The dispersion was then sprayed on the hydrophobic agent of the sponge-ink self-floating evaporator and dried in an oven at 80°C for 2 h to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material, named Al:STO / sponge-ink self-floating evaporator-20, denoted as Al:STO / CIMS-20.

[0056] Example 2

[0057] The preparation method of the photothermal interface evaporation-photocatalytic hydrogen production composite material Al: STO / sponge-ink self-floating evaporator-50 is the same as the preparation steps of Example 1, except that the mass of Al: STO is replaced from 20 mg to 50 mg, and includes the following steps:

[0058] Step 1, preparation of Al:STO:

[0059] SrTiO3 nanoparticles were prepared by a hydrothermal method. The specific process was as follows: Under stirring conditions, 10 mL of a 0.5 mol / L aqueous strontium nitrate solution was added dropwise to a 10 mL of a 0.5 mol / L ethylene glycol solution of tetra-n-butyl titanate, and then 10 mL of a 5 mol / L NaOH solution was added. After stirring for 30 min, a mixed solution was obtained. The mixed solution was transferred to the inner lining of a hydrothermal autoclave with a volume of 100 mL. After sealing, the mixed solution was placed in an oven at 200°C for reaction for 24 h. After the reaction was completed, the mixture was cooled to room temperature. The obtained white precipitate was subjected to multiple centrifugal washing treatments until it was neutral, and finally vacuum dried and collected to obtain SrTiO3 nanoparticles.

[0060] Al:STO was prepared by the molten salt method, and the specific process was as follows: SrTiO3 nanoparticles, alumina and strontium chloride were mixed and ground for 30 minutes in a molar ratio of 1:0.02:10 to obtain a mixture, and then the mixture was transferred to a corundum crucible and calcined at 1100°C for 5 hours in a muffle furnace with a heating rate of 5°C / min. After the reaction was completed, it was naturally cooled to room temperature and then washed with deionized water to remove the residual strontium chloride. Finally, it was vacuum dried and collected to obtain Al-doped SrTiO3 nanoparticles.

[0061] The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 100 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.3 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 1.0 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.3 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 1.0 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution. 2After 1 h of xenon lamp irradiation, 0.2 mol / L K2CrO4 solution containing 1 wt% Cr was added and the irradiation was continued at 300 mW / cm 2 The xenon lamp was irradiated for 1 h, and the entire photodeposition process was maintained at 35 o C. After the reaction, the particles were washed with water and vacuum dried to obtain Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalysts, named Al:STO.

[0062] Step 2: Preparation of sponge-ink self-floating evaporator:

[0063] 5 mL of ink was dispersed in a surface dish with a diameter of 5 cm, and a melamine sponge with a size of 3.5 cm × 3.5 cm × 1 cm was immersed in the ink to allow the bottom of the melamine sponge to fully absorb the ink, and then placed in an oven at 80°C for 2 hours to be dried to obtain a treated absorbent sponge. The treated absorbent sponge was a melamine sponge adsorbed with ink.

[0064] 2 mg of polydimethylsiloxane and 0.2 mg of curing agent were ultrasonically dispersed in a mixed solution of 50 mL of ethanol and n-hexane in a volume ratio of 4:1 to obtain a hydrophobic agent solution. The curing agent was polydimethylsiloxane with hydroxyl groups. 3 mL of the hydrophobic agent solution was sprayed on the ink treated sponge by spraying, and then heated in an oven at 120°C for 2 h to obtain a sponge-ink self-floating evaporator, named CIMS.

[0065] Step 3, Preparation of Al:STO / sponge-ink self-floating evaporator-50:

[0066] The coupling system was prepared by a simple spraying method. 50 mg of Al:STO prepared in step 1 was ultrasonically dispersed in 5 mL of ethanol to obtain a dispersion. The dispersion was then sprayed on the surface of the sponge-ink self-floating evaporator and dried in an oven at 80°C for 2 h to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material, named Al:STO / sponge-ink self-floating evaporator-50, denoted as Al:STO / CIMS-50.

[0067] Example 3

[0068] The preparation method of the photothermal interface evaporation-photocatalytic hydrogen production composite material Al: STO / sponge-ink self-floating evaporator-100 is the same as the preparation steps of Example 1, except that the mass of Al: STO is replaced from 20 mg to 100 mg, and includes the following steps:

[0069] Step 1, preparation of Al:STO:

[0070] SrTiO3 nanoparticles were prepared by a hydrothermal method. The specific process was as follows: Under stirring conditions, 10 mL of a 0.5 mol / L aqueous strontium nitrate solution was added dropwise to a 10 mL of a 0.5 mol / L ethylene glycol solution of tetra-n-butyl titanate, and then 10 mL of a 5 mol / L NaOH solution was added. After stirring for 30 min, a mixed solution was obtained. The mixed solution was transferred to the inner lining of a hydrothermal autoclave with a volume of 100 mL. After sealing, the mixed solution was placed in an oven at 200°C for reaction for 24 h. After the reaction was completed, the mixture was cooled to room temperature. The obtained white precipitate was subjected to multiple centrifugal washing treatments until it was neutral, and finally vacuum dried and collected to obtain SrTiO3 nanoparticles.

[0071] Al:STO was prepared by the molten salt method, and the specific process was as follows: SrTiO3 nanoparticles, alumina and strontium chloride were mixed and ground for 30 minutes in a molar ratio of 1:0.02:10 to obtain a mixture, and then the mixture was transferred to a corundum crucible and calcined at 1100°C for 5 hours in a muffle furnace with a heating rate of 5°C / min. After the reaction was completed, it was naturally cooled to room temperature and then washed with deionized water to remove the residual strontium chloride. Finally, it was vacuum dried and collected to obtain Al-doped SrTiO3 nanoparticles.

[0072] The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 100 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.3 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 1.0 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.3 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 1.0 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution. 2 After 1 h of xenon lamp irradiation, 0.2 mol / L K2CrO4 solution containing 1 wt% Cr was added and the irradiation was continued at 300 mW / cm 2 The xenon lamp was irradiated for 1 h, and the entire photodeposition process was maintained at 35 o C. After the reaction, the particles were washed with water and vacuum dried to obtain Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalysts, named Al:STO.

[0073] Step 2: Preparation of sponge-ink self-floating evaporator:

[0074] 5 mL of ink was dispersed in a surface dish with a diameter of 5 cm, and a melamine sponge with a size of 3.5 cm × 3.5 cm × 1 cm was immersed in the ink to allow the bottom of the melamine sponge to fully absorb the ink, and then placed in an oven at 80°C for 2 hours to be dried to obtain a treated absorbent sponge. The treated absorbent sponge was a melamine sponge adsorbed with ink.

[0075] 2 mg of polydimethylsiloxane and 0.2 mg of curing agent were ultrasonically dispersed in a mixed solution of 50 mL of ethanol and n-hexane in a volume ratio of 4:1 to obtain a hydrophobic agent solution. The curing agent was polydimethylsiloxane with hydroxyl groups. 3 mL of the hydrophobic agent solution was sprayed on the ink treated sponge by spraying, and then heated in an oven at 120°C for 2 h to obtain a sponge-ink self-floating evaporator, named CIMS.

[0076] Step 3, Preparation of Al:STO / sponge-ink self-floating evaporator-100:

[0077] The coupling system was prepared by a simple spraying method. 100 mg of Al:STO prepared in step 1 was ultrasonically dispersed in 5 mL of ethanol to obtain a dispersion. The dispersion was then sprayed on the surface of the sponge-ink self-floating evaporator and dried in an oven at 80°C for 2 h to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material, named Al:STO / sponge-ink self-floating evaporator-100, denoted as Al:STO / CIMS-100.

[0078] Example 4

[0079] The preparation method of the photothermal interface evaporation-photocatalytic hydrogen production composite material Al: STO / sponge-ink self-floating evaporator-150 is the same as the preparation steps of Example 1, except that the mass of Al: STO is replaced from 20 mg to 150 mg, and comprises the following steps:

[0080] Step 1, preparation of Al:STO:

[0081] SrTiO3 nanoparticles were prepared by a hydrothermal method. The specific process was as follows: Under stirring conditions, 10 mL of a 0.5 mol / L aqueous strontium nitrate solution was added dropwise to a 10 mL of a 0.5 mol / L ethylene glycol solution of tetra-n-butyl titanate, and then 10 mL of a 5 mol / L NaOH solution was added. After stirring for 30 min, a mixed solution was obtained. The mixed solution was transferred to the inner lining of a hydrothermal autoclave with a volume of 100 mL. After sealing, the mixed solution was placed in an oven at 200°C for reaction for 24 h. After the reaction was completed, the mixture was cooled to room temperature. The obtained white precipitate was subjected to multiple centrifugal washing treatments until it was neutral, and finally vacuum dried and collected to obtain SrTiO3 nanoparticles.

[0082] Al:STO was prepared by the molten salt method, and the specific process was as follows: SrTiO3 nanoparticles, alumina and strontium chloride were mixed and ground for 30 minutes in a molar ratio of 1:0.02:10 to obtain a mixture, and then the mixture was transferred to a corundum crucible and calcined at 1100°C for 5 hours in a muffle furnace with a heating rate of 5°C / min. After the reaction was completed, it was naturally cooled to room temperature and then washed with deionized water to remove the residual strontium chloride. Finally, it was vacuum dried and collected to obtain Al-doped SrTiO3 nanoparticles.

[0083] The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 100 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.3 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 1.0 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.3 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition under stirring conditions. 2 After 1 h of xenon lamp irradiation, 0.2 mol / L K2CrO4 solution containing 1 wt% Cr was added and the irradiation was continued at 300 mW / cm 2 The xenon lamp was irradiated for 1 h, and the entire photodeposition process was maintained at 35 o C. After the reaction, the particles were washed with water and collected by vacuum drying to obtain Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalysts, named Al:STO.

[0084] Step 2: Preparation of sponge-ink self-floating evaporator:

[0085] 5 mL of ink was dispersed in a surface dish with a diameter of 5 cm, and a melamine sponge with a size of 3.5 cm × 3.5 cm × 1 cm was immersed in the ink to allow the bottom of the melamine sponge to fully absorb the ink, and then placed in an oven at 80°C for 2 hours to be dried to obtain a treated absorbent sponge. The treated absorbent sponge was a melamine sponge adsorbed with ink.

[0086] 2 mg of polydimethylsiloxane and 0.2 mg of curing agent were ultrasonically dispersed in a mixed solution of 50 mL of ethanol and n-hexane in a volume ratio of 4:1 to obtain a hydrophobic agent solution. The curing agent was polydimethylsiloxane with hydroxyl groups. 3 mL of the hydrophobic agent solution was sprayed on the ink treated sponge by spraying, and then heated in an oven at 120°C for 2 h to obtain a sponge-ink self-floating evaporator, named CIMS.

[0087] Step 3, Preparation of Al:STO / sponge-ink self-floating evaporator-150:

[0088] The coupling system was prepared by a simple spraying method. 150 mg of Al:STO prepared in step 1 was ultrasonically dispersed in 5 mL of ethanol to obtain a dispersion. The dispersion was then sprayed on the surface of the sponge-ink self-floating evaporator and dried in an oven at 80°C for 2 h to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material, named Al:STO / sponge-ink self-floating evaporator-150, denoted as Al:STO / CIMS-150.

[0089] Example 5

[0090] The preparation method of the photothermal interface evaporation-photocatalytic hydrogen production composite material comprises the following steps:

[0091] Step 1, preparation of Al:STO:

[0092] SrTiO3 nanoparticles were prepared by a hydrothermal method. The specific process was as follows: Under stirring conditions, 10 mL of a 0.5 mol / L aqueous strontium nitrate solution was added dropwise to a 10 mL of a 0.5 mol / L ethylene glycol solution of tetra-n-butyl titanate, and then 10 mL of a 5 mol / L NaOH solution was added. After stirring for 30 min, a mixed solution was obtained. The mixed solution was transferred to the inner lining of a hydrothermal autoclave with a volume of 100 mL. After sealing, the mixed solution was placed in an oven at 200°C for reaction for 24 h. After the reaction was completed, the mixture was cooled to room temperature. The obtained white precipitate was subjected to multiple centrifugal washing treatments until it was neutral, and finally vacuum dried and collected to obtain SrTiO3 nanoparticles.

[0093] Al:STO was prepared by the molten salt method, and the specific process was as follows: SrTiO3 nanoparticles, alumina and strontium chloride were mixed and ground for 30 minutes in a molar ratio of 1:0.5:15 to obtain a mixture, and then the mixture was transferred to a corundum crucible and calcined at 1150°C in a muffle furnace for 8 hours with a heating rate of 5°C / min. After the reaction was completed, it was naturally cooled to room temperature and then washed with deionized water to wash away the residual strontium chloride. Finally, it was vacuum dried and collected to obtain Al-doped SrTiO3 nanoparticles.

[0094] The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 100 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.1 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. ... 2 After 1 h of xenon lamp irradiation, 0.5 wt% Cr in 0.2 mol / L K2CrO4 solution was added and the irradiation was continued at 800 mW / cm 2 The xenon lamp was irradiated for 0.5 h, and the entire photodeposition process was maintained at 35o C. After the reaction, the particles were washed with water and vacuum dried to obtain Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalysts, named Al:STO.

[0095] Step 2: Preparation of sponge-ink self-floating evaporator:

[0096] 5 mL of ink was dispersed in a surface dish with a diameter of 5 cm, and a melamine sponge with a size of 3.5 cm × 3.5 cm × 1 cm was immersed in the ink to allow the bottom of the melamine sponge to fully absorb the ink, and then placed in an oven at 80°C for 2 hours to be dried to obtain a treated absorbent sponge. The treated absorbent sponge was a melamine sponge adsorbed with ink.

[0097] 2 mg of polydimethylsiloxane and 0.2 mg of curing agent were ultrasonically dispersed in a mixed solution of 50 mL of ethanol and n-hexane in a volume ratio of 4:1 to obtain a hydrophobic agent solution. The curing agent was polydimethylsiloxane with a hydrogen group. 3 mL of the hydrophobic agent solution was sprayed on the ink treated sponge by a spraying method, and then heated in an oven at 120°C for 2 h to obtain a sponge-ink self-floating evaporator.

[0098] Step 3: Preparation of photothermal interface evaporation-photocatalytic hydrogen production composite material:

[0099] The coupling system was prepared by a simple spraying method. 100 mg of Al:STO prepared in step 1 was ultrasonically dispersed in 5 mL of ethanol to obtain a dispersion. The dispersion was then sprayed on the hydrophobic agent of the sponge-ink self-floating evaporator and dried in an oven at 80°C for 2 h to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material.

[0100] Example 6

[0101] The preparation method of the photothermal interface evaporation-photocatalytic hydrogen production composite material comprises the following steps:

[0102] Step 1, preparation of Al:STO:

[0103] SrTiO3 nanoparticles were prepared by a hydrothermal method. The specific process was as follows: Under stirring conditions, 10 mL of a 0.5 mol / L aqueous strontium nitrate solution was added dropwise to a 10 mL of a 0.5 mol / L ethylene glycol solution of tetra-n-butyl titanate, and then 10 mL of a 5 mol / L NaOH solution was added. After stirring for 30 min, a mixed solution was obtained. The mixed solution was transferred to the inner lining of a hydrothermal autoclave with a volume of 100 mL. After sealing, the mixed solution was placed in an oven at 200°C for reaction for 24 h. After the reaction was completed, the mixture was cooled to room temperature. The obtained white precipitate was subjected to multiple centrifugal washing treatments until it was neutral, and finally vacuum dried and collected to obtain SrTiO3 nanoparticles.

[0104] Al:STO was prepared by the molten salt method, and the specific process was as follows: SrTiO3 nanoparticles, alumina and strontium chloride were mixed in a molar ratio of 1:1:20 and ground for 30 minutes to obtain a mixture, and then the mixture was transferred to a corundum crucible and calcined at 1100°C for 10 hours in a muffle furnace with a heating rate of 5°C / min. After the reaction was completed, it was naturally cooled to room temperature and then washed with deionized water to wash away the residual strontium chloride. Finally, it was vacuum dried and collected to obtain Al-doped SrTiO3 nanoparticles.

[0105] The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 100 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.6 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. ... under stirring conditions. 2 After 10 min of xenon lamp irradiation, 0.05 wt% Cr in 0.2 mol / L K2CrO4 solution was added and the irradiation was continued at 100 mW / cm 2 The xenon lamp was irradiated for 1 h, and the entire photodeposition process was maintained at 35 o C. After the reaction, the particles were washed with water and vacuum dried to obtain Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalysts, named Al:STO.

[0106] Step 2: Preparation of sponge-ink self-floating evaporator:

[0107] 5 mL of ink was dispersed in a surface dish with a diameter of 5 cm, and a melamine sponge with a size of 3.5 cm × 3.5 cm × 1 cm was immersed in the ink to allow the bottom of the melamine sponge to fully absorb the ink, and then placed in an oven at 80°C for 2 hours to be dried to obtain a treated absorbent sponge. The treated absorbent sponge was a melamine sponge adsorbed with ink.

[0108] 2 mg of polydimethylsiloxane and 0.2 mg of curing agent were ultrasonically dispersed in a mixed solution of 50 mL of ethanol and n-hexane in a volume ratio of 4:1 to obtain a hydrophobic agent solution. The curing agent was polydimethylsiloxane with a hydrogen group. 3 mL of the hydrophobic agent solution was sprayed on the ink treated sponge by a spraying method, and then heated in an oven at 120°C for 2 h to obtain a sponge-ink self-floating evaporator.

[0109] Step 3: Preparation of photothermal interface evaporation-photocatalytic hydrogen production composite material:

[0110] The coupling system was prepared by a simple spraying method. 100 mg of Al:STO prepared in step 1 was ultrasonically dispersed in 5 mL of ethanol to obtain a dispersion. The dispersion was then sprayed on the hydrophobic agent of the sponge-ink self-floating evaporator and dried in an oven at 80°C for 2 h to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material.

[0111] Comparative Example 1

[0112] The preparation method of the Al:STO / sponge-ink evaporator-100 of the photothermal interface evaporation-photocatalytic hydrogen production composite material without a hydrophobic agent is the same as the preparation steps of Example 3, except that the hydrophobic agent polydimethylsiloxane and the curing agent are not added during the preparation of the sponge-ink self-floating evaporator, and includes the following steps:

[0113] Step 1, preparation of Al:STO:

[0114] SrTiO3 nanoparticles were prepared by a hydrothermal method. The specific process was as follows: Under stirring conditions, 10 mL of a 0.5 mol / L aqueous strontium nitrate solution was added dropwise to a 10 mL of a 0.5 mol / L ethylene glycol solution of tetra-n-butyl titanate, and then 10 mL of a 5 mol / L NaOH solution was added. After stirring for 30 min, a mixed solution was obtained. The mixed solution was transferred to the inner lining of a hydrothermal autoclave with a volume of 100 mL. After sealing, the mixed solution was placed in an oven at 200°C for reaction for 24 h. After the reaction was completed, the mixture was cooled to room temperature. The obtained white precipitate was subjected to multiple centrifugal washing treatments until it was neutral, and finally vacuum dried and collected to obtain SrTiO3 nanoparticles.

[0115] Al:STO was prepared by the molten salt method, and the specific process was as follows: SrTiO3 nanoparticles, alumina and strontium chloride were mixed and ground for 30 minutes in a molar ratio of 1:0.02:10 to obtain a mixture, and then the mixture was transferred to a corundum crucible and calcined at 1100°C for 5 hours in a muffle furnace with a heating rate of 5°C / min. After the reaction was completed, it was naturally cooled to room temperature and then washed with deionized water to remove the residual strontium chloride. Finally, it was vacuum dried and collected to obtain Al-doped SrTiO3 nanoparticles.

[0116] The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 100 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.3 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 1.0 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution; then, 0.3 wt% of Rh in 0.5 mol / L Na3RhCl6 solution was added according to the stoichiometric ratio under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition under stirring conditions. The Rh / Cr2O3 co-catalyst was loaded by in-situ photodeposition. The specific process was as follows: 1.0 mg of Al-doped SrTiO3 nanoparticles were ultrasonically dispersed into 80 mL of 20 wt% methanol aqueous solution. 2 After 1 h of xenon lamp irradiation, 0.2 mol / L K2CrO4 solution containing 1 wt% Cr was added and the irradiation was continued at 300 mW / cm2 The xenon lamp was irradiated for 1 h, and the entire photodeposition process was maintained at 35 o C. After the reaction, the particles were washed with water and vacuum dried to obtain Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalysts, named Al:STO.

[0117] Step 2: Preparation of Al:STO / sponge-ink evaporator-100 without hydrophobic agent:

[0118] 5 mL of ink was dispersed in a surface dish with a diameter of 5 cm, and a melamine sponge with a size of 3.5 cm × 3.5 cm × 1 cm was immersed in the ink to allow the bottom of the melamine sponge to fully absorb the ink, and then placed in an oven at 80°C for 2 hours to dry, thereby obtaining a melamine sponge adsorbed with ink.

[0119] The melamine sponge adsorbed with ink was used as the sponge-ink evaporator. The coupling system was prepared by a simple spraying method. 100 mg of Al:STO prepared in step 1 was ultrasonically dispersed in 5 mL of ethanol to obtain a dispersion. The dispersion was then sprayed on the surface of the sponge-ink evaporator and dried in an oven at 80 °C for 2 h to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material, which was named Al:STO / sponge-ink evaporator-100 without hydrophobic agent.

[0120] The present invention uses low-cost ink and melamine sponge as photothermal material and water transport channel respectively to construct an efficient solar-driven photothermal interface evaporation-photocatalytic hydrogen production composite material, Al: STO / CIMS-x, x is 20, 50, 100, 150, and the preparation process is as follows Figure 3 As shown, the following is a study using Al:STO of Example 1, CIMS of Example 1, Al:STO / CIMS-20, Al:STO / CIMS-50, Al:STO / CIMS-100 and Al:STO / CIMS-150 of Examples 1 to 4 as examples, and the research methods and results are as follows:

[0121] 1. The present invention couples the interface evaporation system of Al:STO and CIMS for the first time, and successfully constructs a photothermal interface evaporation-photocatalytic hydrogen production composite material. The coupling of Al:STO and CIMS successfully realizes the efficient use of the frequency division of the full spectrum of sunlight, and realizes the continuous conversion of interface evaporation-hydrogen production, such as Figure 1As shown, low-energy photons in the solar spectrum, i.e., long-wave visible light and infrared light, are used to drive the evaporation of seawater interface to obtain fresh water resources; high-energy photons in the solar spectrum, i.e., short-wave visible light and ultraviolet light, are used to drive the photocatalytic decomposition of water to produce hydrogen, thus realizing the efficient use of the frequency division of the full spectrum of sunlight, obtaining fresh water and producing hydrogen at the same time in the process of solar energy conversion, and realizing the continuous conversion of interface evaporation-hydrogen production. The specific analysis is as follows:

[0122] Figure 4 These are the X-ray diffraction patterns of Al:STO, CIMS, Al:STO / CIMS-20, Al:STO / CIMS-50, Al:STO / CIMS-100 and Al:STO / CIMS-150, among which the diffraction peak of Al:STO belongs to the typical cubic perovskite structure, JCPDS No.00-035-0734, and the space group is Pm3m. The XRD pattern of Al:STO is consistent with the PDF standard card of SrTiO3 very well, indicating that the doping of Al element has not changed the basic structure of SrTiO3. The sharp diffraction peak shows that the Al:STO prepared by the molten salt method has good crystallinity.

[0123] CIMS is only at 22.3 o There is a faint peak on the left and right, which is related to its carbon material, while Al:STO / CIMS-20, Al:STO / CIMS-50, Al:STO / CIMS-100 and Al:STO / CIMS-150 have both the peak of CIMS substrate and the sharp diffraction peak of Al:STO, and with the increase of Al:STO dosage, the diffraction peak of Al:STO in the coupling system sample becomes stronger, indicating that the spraying method adopted in the present invention successfully loads Al:STO on the surface of CIMS and constructs a photothermal interface evaporation-photocatalytic hydrogen production composite material.

[0124] The light absorption of different components in the sample directly determines the distribution of incident sunlight. In order to analyze the light absorption properties of the coupled system, Fig.10 The UV-Vis spectra of Al:STO and Al:STO / CIMS-100 are shown in Figure 2. Fig.10 As shown, Al:STO has a steep absorption edge, and its light absorption cutoff wavelength is around 390nm, with a band gap of 3.19eV, indicating that Al:STO can only utilize the ultraviolet light band in the solar spectrum; while Al:STO / CIMS-100 exhibits strong light absorption properties in the entire 300nm~2000nm band, proving that CIMS can make full use of the energy of the visible and infrared light bands in the solar spectrum and has good photothermal potential. This result also shows that the present invention has successfully achieved the efficient utilization of the full spectrum of sunlight by frequency division.

[0125] Evaporation performance test method: add seawater into a glass beaker, then place the photothermal interface evaporation-photocatalytic hydrogen production composite material in the water, using an intensity of 100mW / cm 2 A xenon lamp simulates sunlight and radiates it onto the photothermal interface evaporation-photocatalytic hydrogen production composite material. The change in water mass loss is recorded on an electronic analytical balance with an accuracy of 0.001g every 10 minutes.

[0126] Hydrogen production performance test method: put water and photothermal interface evaporation-photocatalytic hydrogen production composite material into a closed reaction container, and the photothermal interface evaporation-photocatalytic hydrogen production composite material will float on the water surface. The use intensity is 100mW / cm 2 A xenon lamp was used to simulate sunlight, and the radiation was irradiated onto the photothermal interface evaporation-photocatalytic hydrogen production composite material. A sample was taken once every hour using a micro-injector and injected into a gas chromatograph to calculate the amount of H2 produced.

[0127] Fig.11 The evaporation performance and hydrogen production performance test results of CIMS and Al:STO / CIMS-100 are shown in Figure 2. Fig.11 As shown in Figure (a), CIMS exhibits good evaporation performance, and its vapor generation rate can reach 1.365 kg m -2 h -1 ;like Fig.11 As shown in Figure (b), after Al:STO was introduced on the CIMS surface, the evaporation performance of the coupled system was reduced, but it had the ability to produce hydrogen by splitting water, and the rate of hydrogen production by splitting water reached 6.27 mmol m -2 h -1 , indicating that the present invention successfully achieves the simultaneous acquisition of fresh water resources and hydrogen energy.

[0128] 2. The addition of polydimethylsiloxane hydrophobic agent on the surface ensures the hydrophobicity of the surface of the photothermal interface evaporation-photocatalytic hydrogen production composite material, enabling it to float on the water surface for a long time. The specific analysis is as follows:

[0129] In order to make the photothermal interface evaporation-photocatalytic hydrogen production composite material float on the surface of the water body and improve its salt resistance, the present invention sprays a hydrophobic layer of polydimethylsiloxane on the photothermal interface evaporation-photocatalytic hydrogen production composite material. In order to explore the effect of the hydrophobic agent, the contact angle test of the photothermal interface evaporation-photocatalytic hydrogen production composite material is carried out. The results are as follows Figure 8 As shown, Figure 8The side view of the contact angle of Al:STO / sponge-ink evaporator-100 without hydrophobic agent in comparative example 1 and Al:STO / CIMS-100 in example 3. Among them, Al:STO / sponge-ink evaporator-100 without hydrophobic agent completely absorbs water droplets within 0.4s, indicating that when polydimethylsiloxane hydrophobic agent is not added, Al:STO / sponge-ink evaporator-100 without hydrophobic agent exhibits excellent hydrophilicity, which is mainly due to the loose and porous structure of melamine sponge, which can provide abundant channels for the transport of water. In contrast, after adding the hydrophobic agent polydimethylsiloxane, the Al:STO / CIMS-100 of Example 3 exhibited strong hydrophobic properties, and the contact angle between the upper surface and water was 148°, indicating that the upper surface of Al:STO / CIMS-100 had excellent hydrophobicity, and the melamine sponge itself had good hydrophilicity, which successfully constructed a Janus membrane on the upper surface of Al:STO / CIMS-100. On the one hand, the hydrophobicity of the upper surface of the Janus membrane ensured that it could float on the water surface for a long time and avoid the accumulation of salt on the upper surface. On the other hand, the hydrophilicity of the lower surface of the Janus membrane could continuously supply seawater.

[0130] In order to verify the effect of the hydrophobic agent, the floating characteristics of Al:STO / sponge-ink evaporator-100 and Al:STO / CIMS-100 without hydrophobic agent were tested. Fig. 9 The side view and top view of Al:STO / sponge-ink evaporator-100 and Al:STO / CIMS-100 without hydrophobic agent were placed in water for 60 seconds. Among them, Al:STO / sponge-ink evaporator-100 without hydrophobic agent showed strong hydrophilicity. After being placed in water for 60 seconds, the sample gradually absorbed water and sank, and the upper surface was immersed below the water surface. It could not float on the water surface for a long time. Under light, the entire water body would be heated, and interfacial evaporation could not be achieved. In contrast, after adding the hydrophobic agent, the upper surface of Al:STO / CIMS-100 always remained above the liquid surface, and the contact angle of the upper surface was 148°, showing strong hydrophobicity, and it could float on the water surface for a long time, realizing the continuous conversion of interfacial evaporation-hydrogen production.

[0131] 3. The loading amount of Al:STO has a great influence on the hydrogen production performance of Al:STO / CIMS-100. The specific analysis is as follows:

[0132] Fig.12The bar graphs are the hydrogen production rates of CIMS, Al:STO / CIMS-20, Al:STO / CIMS-50, Al:STO / CIMS-100 and Al:STO / CIMS-150. When the Al:STO loading is between 0 mg and 100 mg, the hydrogen production rate increases with the increase of the Al:STO loading, and when the Al:STO loading is 100 mg, the highest hydrogen production rate reaches 6.27 mmol m -2 h -1 ; However, when the Al:STO loading exceeds 100 mg, the hydrogen production rate is greatly reduced. It is speculated that the excessive catalyst loading affects the water evaporation rate.

[0133] The present invention loads Al:STO on the surface of CIMS and successfully constructs a photothermal interface evaporation-photocatalytic hydrogen production composite material. The coupled system can float on the water surface for a long time, realizing the continuous conversion function of interface evaporation-hydrogen production. Among them, Al:STO can use the ultraviolet light band in the solar spectrum, that is, high-energy photons to decompose pure water to produce hydrogen; while CIMS can make full use of the visible light and infrared light bands in the solar spectrum, that is, the energy of low-energy photons, successfully realizing the frequency division and efficient utilization of the full spectrum of sunlight, and realizing the simultaneous acquisition of fresh water resources and hydrogen.

[0134] 4. The present invention further analyzes the structure and performance of Al:STO, CIMS, Al:STO / CIMS-20, Al:STO / CIMS-50, Al:STO / CIMS-100 and Al:STO / CIMS-150. The specific analysis is as follows:

[0135] Figure 5 Figure (a) is a scanning electron microscope image of Al-doped SrTiO3 nanoparticles. Figure 5 Figure (b) is a transmission electron microscope image of Al-doped SrTiO3 nanoparticles. The Al-doped SrTiO3 nanoparticles are composed of cubic particles of different sizes, and the particle size is mostly between 100nm and 1μm, which is consistent with existing literature reports; such a crystal structure makes the Al-doped SrTiO3 nanoparticles have a stable perovskite structure. At the same time, since the preparation temperature of Al-doped SrTiO3 nanoparticles is 1100℃, which is higher than the general catalyst preparation temperature, it can provide the necessary conditions for further optimization of performance and loading of other catalysts in the future.

[0136] Figure 6 Figure (a) is a top view of Al:STO / CIMS-100 of Example 3. Figure 6Figure (b) is a side view of Al:STO / CIMS-100 of Example 3. The entire Al:STO / CIMS-100 is based on melamine sponge. Its fluffy and porous nature and good hydrophilicity enable it to serve as a good water transport channel. Seawater can gradually diffuse to the upper surface through capillary action. The black part on the upper surface of Al:STO / CIMS-100 is caused by the deposition of carbon nanoparticles in the ink. It is a good light-absorbing material that can fully absorb visible light and infrared light in the solar spectrum and has excellent photothermal properties. It heats the water transported to the upper surface and promotes its rapid evaporation into water vapor.

[0137] In order to observe and analyze the surface morphology of the photothermal interface evaporation-photocatalytic hydrogen production composite material more clearly, the surface of the photothermal interface evaporation-photocatalytic hydrogen production composite material was analyzed by ultra-depth of field images. Figure 7 These are super depth of field photos of melamine sponge, CIMS, Al:STO / CIMS-20, Al:STO / CIMS-50, Al:STO / CIMS-100, and Al:STO / CIMS-150. For the melamine sponge without any load, its surface is a loose and porous structure, which provides sufficient physical space for the loading of photothermal materials and photocatalyst materials on the one hand, and on the other hand, the porous structure also provides a channel for the rapid transport of water. After the ink was introduced to obtain CIMS, obvious black substances appeared on the surface of the melamine sponge, indicating that the carbon material in the ink was successfully loaded on the skeleton of the sponge. After further introduction of Al:STO, white granular substances appeared on the surfaces of Al:STO / CIMS-20, Al:STO / CIMS-50, Al:STO / CIMS-100 and Al:STO / CIMS-150, proving the successful loading of Al:STO. As the loading amount of Al:STO increased, the amount of white particles in the samples gradually increased. Al:STO has excellent complete water splitting performance under ultraviolet light, and can completely decompose water or water vapor on its surface to produce hydrogen and oxygen.

[0138] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a photothermal interface evaporation-photocatalytic hydrogen production composite material, characterized in that: The steps include: Taking an absorbent sponge as a base, immersing the absorbent sponge in ink so that the bottom of the absorbent sponge absorbs the ink, and then drying it to obtain a treated absorbent sponge; After dispersing the hydrophobic agent polydimethylsiloxane, a hydrophobic agent solution is obtained; The hydrophobic agent solution is attached to the ink treated with the water-absorbing sponge, and then dried to obtain a sponge-ink self-floating evaporator; After dispersing the photocatalyst, the photocatalyst is attached to the hydrophobic agent of the sponge-ink self-floating evaporator to obtain a photothermal interface evaporation-photocatalytic hydrogen production composite material; The photocatalyst is Al-doped SrTiO3 nanoparticles loaded with Rh / Cr2O3 co-catalyst; The volume ratio of the sponge-ink self-floating evaporator to the mass ratio of the photocatalyst is (3.5 cm×3.5 cm×1 cm): 20 mg to 150 mg.

2. The method for preparing the photothermal interface evaporation-photocatalytic hydrogen production composite material according to claim 1, characterized in that: A curing agent is also added during the preparation of the hydrophobic agent solution. The curing agent is polydimethylsiloxane with hydroxyl groups. The mass ratio of the curing agent to the hydrophobic agent is 1:10-20.

3. The method for preparing the photothermal interface evaporation-photocatalytic hydrogen production composite material according to claim 1, characterized in that: The photocatalyst was prepared according to the following steps: SrTiO3 nanoparticles were prepared by hydrothermal method using aqueous solution of strontium nitrate and ethylene glycol solution of tetra-n-butyl titanate as raw materials. SrTiO3 nanoparticles and alumina are used as raw materials, strontium chloride is used as molten salt, and after grinding and mixing evenly, they are calcined at high temperature. The strontium chloride in the molten state causes the SrTiO3 nanoparticles to grow again, and grow into Al-doped SrTiO3 nanoparticles with cubic block morphology; Al-doped SrTiO3 nanoparticles are ultrasonically dispersed in a solvent to obtain a dispersion, and then a Na3RhCl6 solution is added thereto, and Rh is photodeposited on the Al-doped SrTiO3 nanoparticles after light irradiation. Then a K2CrO4 solution is added to the dispersion, and Cr2O3 is photodeposited on the Al-doped SrTiO3 nanoparticles after light irradiation to obtain a photocatalyst.

4. The method for preparing the photothermal interface evaporation-photocatalytic hydrogen production composite material according to claim 3, characterized in that: The mass percentages of Al-doped SrTiO3 nanoparticles in the dispersion, Rh in the Na3RhCl6 solution, and Cr in the K2CrO4 solution are 100:0.1-0.6:0.05-1.

5. The method for preparing the photothermal interface evaporation-photocatalytic hydrogen production composite material according to claim 3, characterized in that: The intensity of light irradiation is 100mW / cm 2 ~800mW / cm 2 The irradiation time is 10min~60min.

6. The method for preparing the photothermal interface evaporation-photocatalytic hydrogen production composite material according to claim 3, characterized in that: The molar ratio of SrTiO3 nanoparticles, aluminum oxide and strontium chloride is 1:0.02 to 1:10 to 20.

7. The method for preparing the photothermal interface evaporation-photocatalytic hydrogen production composite material according to claim 3, characterized in that: The conditions for high temperature calcination are: calcination at 1100°C to 1150°C for 5h to 10h.

8. A photothermal interface evaporation-photocatalytic hydrogen production composite material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the photothermal interface evaporation-photocatalytic hydrogen production composite material as claimed in claim 8 in preparing materials for photocatalytic water splitting to produce hydrogen and in preparing materials for driving seawater interface evaporation.